STUDY OF FERRONICKEL PARTICLE FORMATION FROM SAPROLITIC NICKEL ORE AT TEMPERATURE OF 900-1250OC WITH COAL AND CaO, CaF2, AND H3BO3 ADDITION - SHALAT - Nim: 12514047 , WINDU
Nickel is a prominent metal that is found to be useful in everyday activity such us in the field of architecture, construction, household, military, and industry in general. Nowadays, almost 60% of nickel is produced from sulphide ore and the rest of them is produced from laterite ore. The weakness of the process currently commercially employed in lateritic nickel ore processing are the high energy and the capital cost, high reagent consumption, corrosive, and finally the high operational cost so a cheaper and lower cost method for processing nickel ore is required. One of the method to process lateritic nickel ore is by reduction in lower temperature so ferronickel particles are formed, then the particles are separated using magnetic separator. The ore that is used in this research is saprolitic nickel ore from southeast Sulawesi. The saprolitic nickel ore is then analyzed with XRD and XRF to determine the dominant mineral and its chemical composition. Proximate and ultimate analysis is conducted on the coal. This research is conducted to study the formation of ferronickel particles at 900 – 1250oC with the addition of CaO, CaF2, and H3BO3 additives. The reduction is done on 3 kinds of lateritic nickel composite briquette, which is briquette A (10% coal and 10% CaO additive added), briquette B (10% coal, 10% CaO and 10% CaF2 additives added), and briquette C (10% coal, 10% CaO, 10% CaF2, and 10% H3BO3 additives added). The reduction process is done on tube furnace for 120 minutes. During reduction, the argon gas is flown for 120 minutes with the flow rate of 1 liter per minute. After reduction, the briquettes are analyzed with optical microscope and ImageJ package program to determine the formed ferronickel particles size. The reduced briquettes are also analyzed with SEM-EDS. The study results showed that when the reduction was carried out at 1250 C, the A briquette produces a maximum size of ferronickel particles of 18.09 µm. However, when 10% CaO and 10% CaF2 were added (in the briquette B), the maximum of ferronickel particles was increased to 120.515 um. When 10% CaO, 10% CaF2 and 10% H3BO3 were added, the maximum size of ferronickel particles was increased to 277.588 µm. The increased temperatures was followed by the increased size on ferronickel particles. According to SEM-EDS analysis, ferronickel particles in the briquette B after being reduced at the temperature of 1250oC contains iron and nickel respectively 87.61% and 9.24%. Meanwhile, the nickel particles in the briquette C contains iron and nickel respectively 85.65% and 8, 59%.